Psychomotor Agitation in Critically Ill Patients and the Role of Sedation - M. Fedarau; F. Compolo; P. J. Papadakos (Общая реаниматология)
Critically ill patients often receive analgesia and sedation to keep them comfortable and to prevent agitation and delirium, which are serious, common and yet frequently underdiagnosed forms of brain dysfunction in intensive care environment with unclear but often unfavorable contribution to patient outcomes. Apart from delirium assessment and screening the most important aspect of ICU management is understanding the drugs given to patients and their specific advantages and disadvantages. It is crucial for clinicians and units to develop guidelines and protocols for the administration of sedatives depending on the type of patient population. Newer drugs, such as dexmedetomidine and remifentanyl, should be introduced and extensively studied. The immunomodulating effects of sedation also must be explored, as these properties may greatly affect outcome. With an increased understanding of sedative drugs will come an improved ability to use multiple drugs at specific times during the course of hospital treatment. Key words: delirium, sedation, analgesia.